1973
DOI: 10.1128/jb.113.1.322-328.1973
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Labeling Studies on the Membrane of a Facultative Thermophilic Bacillus

Abstract: Spin-labeling studies were conducted to elucidate the rigidity and viscosity of the membrane of a facultative thermophilic bacillus. By employing nitroxide stearate probes, it was observed that this fatty acid was incorporated into the membrane fraction. Electron spin resonance spectroscopy indicated that cells grown at 55 C contained a membrane which was more rigid and viscous than the membrane from cells grown at 37 C. 322 on July 31, 2020 by guest

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
7
0

Year Published

1973
1973
1988
1988

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
3
7
0
Order By: Relevance
“…A decrease in the total amount of branched fatty acids with increasing growth temperature has been reported in several investigations of Bacillus species (4,8,44,47,52,56). This trend was most obvious in B. stearothermophilus (8,47,56) and was, in this species, accompanied by a drastic increase in the amount of n-C16.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…A decrease in the total amount of branched fatty acids with increasing growth temperature has been reported in several investigations of Bacillus species (4,8,44,47,52,56). This trend was most obvious in B. stearothermophilus (8,47,56) and was, in this species, accompanied by a drastic increase in the amount of n-C16.…”
Section: Discussionmentioning
confidence: 72%
“…The fatty acid compositions of lipids from Bacillus species grown at different temperatures have been investigated (4,8,22,44,47,52,56). The species most commonly used was B. stearothermophilus.…”
mentioning
confidence: 99%
“…Brock (19) has suggested that changes of this nature might therefore provide the organism with a more stable membrane. A recent study using spin-labeling techniques (34,35) suggested that membranes prepared from facultative thermophiles grown at 55 C are more rigid than the membranes of cells grown at 37 C. Another study (102) including the same organism demonstrated significant differences in the cell walls of cells grown at 37 and 55 C. Differences were found in chemical composition, susceptibility to lysozyme, and morphological changes observable by electron microscopy. These studies support Brock's hypothesis and suggest that differences do occur in the membranes and cell walls of thermophiles and mesophiles.…”
Section: Lipids Heilbrunn (59) Andmentioning
confidence: 99%
“…However, the ratios of isoto anti-iso-branched-chain fatty acids in these samples also increased with distance from the injection site. This ratio has been found to increase when facultatively thermophilic bacilli are exposed to increasing temperatures (8,43). High hydrostatic pressures may also induce changes in the fatty acids of bacteria, but they lead to an increase in the unsaturated/saturated fatty acid ratio (15).…”
Section: Downloaded Frommentioning
confidence: 99%